Inhibition of vascular smooth muscle growth via signaling crosstalk between AMP-activated protein kinase and cAMP-dependent protein kinase - Stone, Joshua D.; Narine, Avinash; Tulis, David A. (Frontiers in Physiology, 2012)
Abnormal vascular smooth muscle (VSM) growth is central in the pathophysiology of vascular disease yet fully effective therapies to curb this growth are lacking. Recent findings from our lab and others support growth control of VSM by adenosine monophosphate (AMP)-based approaches including the metabolic sensor AMP-activated protein kinase (AMPK) and cAMP-dependent protein kinase (PKA). Molecular crosstalk between AMPK and PKA has been previously suggested, yet the extent to which this occurs and its biological significance in VSM remains unclear. Considering their common AMP backbone and similar signaling characteristics, we hypothesized that crosstalk exists between AMPK and PKA in the regulation of VSM growth. Using rat primary VSM cells, the AMPK agonist AICAR increased AMPK activity and phosphorylation of the catalytic Thr172 site on AMPK. Interestingly, AICAR also phosphorylated a suspected PKA-inhibitory Ser485 site on AMPK, and these cumulative events were reversed by the PKA inhibitor PKI suggesting possible PKA-mediated regulation of AMPK. AICAR also increased PKA activity in a reversible fashion. The cAMP stimulator forskolin increased PKA activity and completely ameliorated Ser/Thr protein phosphatase-2C activity, suggesting a potential mechanism of AMPK modulation by PKA since inhibition of PKA by PKI reduced AMPK activity. Functionally, AMPK inhibited serum-stimulated cell cycle progression and cellular proliferation; however, PKA failed to do so. Moreover, AMPK and PKA reduced PDGF-β-stimulated VSM cell migration. Collectively, these results show that AMPK is capable of reducing VSM growth in both anti-proliferative and anti-migratory fashions. Furthermore, these data suggest that AMPK may be modulated by PKA and that positive feedback may exist between these two systems. These findings reveal a discrete nexus between AMPK and PKA in VSM and provide basis for metabolically-directed targets in reducing pathologic VSM growth.